WAYS OF CREATIVE REALIZATION OF G. VASHCHENKO’S IDEAS ABOUT THE DEVELOPMENT OF WILL AND TEMPER IN THE PROCESS OF PHYSICAL EDUCATION IN THE PRACTICE OF A TEACHER OF PHYSICAL CULTURE - Olena D. Hauriak; Antonina М. Bohdanyuk; Oksana М. Kyselytsia (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
According to the «Concept of education development for 2015-2025» (2015), «The concept of national-patriotic education of children and youth» (2015), according to the «Conceptual principles of secondary education reform» New Ukrainian School»» (2016), one of the strategic tasks of teaching and educating student youth is the formation of a free, spiritually developed personality, and the priority of education, including physical education, is the education of a strong-willed, courageous personality capable of self-development and self-improvement. We believe that these provisions are in line with the ideas and views of the prominent Ukrainian scientist-educator, philosopher and public figure Hryhoriy Hryhorovych Vashchenko (1878–1967), both in the general direction of the professor’s ideas on Ukrainian youth education, and on physical education in particular. This article highlights the ways of creative realization of theoretical and practical ideas of G. Vashchenko on the education of will and character in the process of physical education in the practical work of a physical education teacher of a modern school. The following methods were used in the study: general scientific (analysis, synthesis, comparison, generalization, analogy) – to substantiate the relevance of the study, to define the conceptual and categorical apparatus, to formulate conclusions; comparative-historical (chronological, problem-thematic and logical-historical method) – for an objective analysis of theoretical and practical ideas of G. Vashchenko on the system of physical education and the use of physical education to educate the will and character of Ukrainian youth; empirical (method of studying pedagogical scientific literature, historiographic, search and bibliographic analysis) – for analysis, systematization and generalization of the source base, coverage of scientific achievements of G. Vashchenko; hermeneutic interpretation – to comment on the works and interpret the scientific views of G. Vashchenko on the education of the will and temper of Ukrainian youth by means of physical education. The creative use of theoretical and practical ideas of an outstanding teacher in the modern school, the introduction of Ukrainian traditions and rites, the introduction of national culture into physical education of schoolchildren – national games, dances, entertainments, hiking, excursions, physical culture and improving actions, sports competitions, giving lectures, conversations based on the heroic and patriotic experience; the use of the latest technologies, taking into account the hygienic factors and the ideas of public education – will contribute to the education of discipline, initiative, dignity, patriotism, and most importantly – the education of will and temper. After all, we must remember that a physical education teacher is not a profession, but a lifestyle.